Alpha-synuclein gene polymorphism affects risk of dementia in Han Chinese with Parkinson's disease. (27th July 2019) - Zheng, Jinhua; Zang, Qiuling; Hu, Fengyun; Wei, Hongen; Ma, Jianjun; Xu, Yanming
Highlights: The GG genotype at SNCA rs11931074 significantly reduces the risk of PD. The GG genotype at SNCA rs11931074 significantly increases risk of dementia in PD. Older age, higher UPDRS III score and fewer years of education are associated with higher risk of dementia in PD. Abstract: Background: Single-nucleotide polymorphisms (SNPs) in the SNCA gene encoding alpha-synuclein have been shown to affect the PD phenotype. However, whether such polymorphisms can influence risk of dementia in PD remains unclear. Objectives: To investigate possible associations between SNCA gene polymorphisms and dementia in patients with PD. Materials and methods: A consecutive series of 291 PD patients with dementia (n = 45, 15.5%) or without it (n = 246, 84.5%) were genotyped at four SNPs in the SNCA gene. As controls, 615 healthy Han Chinese were also genotyped. Results: Three SNPs (rs11931074, rs7684318 and rs356219) were in strong linkage disequilibrium. The GG genotype at rs11931074 significantly reduced risk of PD (p = 0.023), but it significantly increased risk of dementia after PD onset (p = 0.015) based on the recessive genetic model. Logistic regression identified the following risk factors for dementia among patients with PD: age ≥65 years (odds ratio [OR] 2.69, 95% confidence interval [CI] 1.25–5.77, p = 0.011), education ≤6 years (OR 4.66, 95% CI 2.21–9.83, p < 0.001), part III score on the Unified Parkinson's Disease Rating Scale ≥40 (OR 5.01, 95% CI 2.40–10.45, p < 0.001), and GG genotype at rs11931074 (OR 2.81, 95% CI 1.16–6.83, p = 0.022). Conclusions: PD patients carrying the protective GG genotype at SNCA rs11931074 may be at significantly higher risk of dementia than patients with other genotypes. Our results support the view that SNCA polymorphisms can have opposite effects on preclinical and clinical PD.